The Relationship Between Hepcidin-Mediated Iron Dysmetabolism and COVID-19 Severity: A Meta-Analysis - Peng, Denggao; Gao, Yanzhang; Zhang, Li; Liu, Zhichao; Wang, Huan; Liu, Yingxia (Frontiers in Public Health, 2022)
Backgrounds Hepcidin has been identified as a systemic iron-regulatory hormone. Recent studies have suggested that iron metabolism disorders may be involved in the pathogenesis of acute respiratory distress syndrome and multiple organ dysfunction in coronavirus disease 2019 (COVID-19). Objectives To re-evaluate the hepcidin-related iron metabolism parameters and explore the relationship between hepcidin-mediated iron dysmetabolism and COVID-19 severity. Methods COVID-19 is classified as mild and moderate as non-severe, severe and critical as severe. A meta-analysis was conducted. Four bibliographic databases were comprehensively searched up to December 31st 2021. Results Six unique studies with data from 477 COVID-19 patients were included. Compared to non-severe cases, severe cases had higher hepcidin (standardized mean difference (SMD), −0.39; 95% Confidence Interval (CI) [−0.76, −0.03]; P = 0.03) and ferritin (SMD, −0.84; 95% CI [−1.30, −0.38]; P = 0.0004). In five out of six studies, a total of 427 patients were tested for serum iron, and there were significant differences in their levels between severe and non-severe cases (SMD, 0.22; 95% CI [0.02, 0.41]; P = 0.03). A total of 320 patients from four out of six studies were tested for transferrin saturation, and the statistical difference was not significant (SMD, 0.06; 95% CI [−0.17, 0.28]; P = 0.64). Conclusion Severe COVID-19 cases had higher serum levels of hepcidin and ferritin, and lower serum iron, without significant differences in transferrin saturation. Further studies are needed to verify whether targeting the hepcidin-mediated iron metabolism axis may influence the outcome and treatment of COVID-19.